The Effect of Current Ratio, Debt To Equity Ratio, Net Profit Margin and Total Asset Turn Over on Earning Growth in Manufacturing Companies in the Mining Sector Listed on the Indonesia Stock Exchange in 2017 – 2019 - Enda Noviyanti Simorangkir; Debora Yosephin Samosir; Desi Fitria (Jurnal Mantik, 2021)
This study aims to see the effect of CR, DER, NPM and TATO on Earning Growth in mining sector manufacturing companies listed on the IDX by using the T test, F test, and using quantitative descriptive. The total population used for this study was 44 companies in the 2017-2019 period and purposive sampling was carried out on the population in order to obtain a sample. The samples obtained were 38 companies. The data analysis technique used in this research is multiple linear regression analysis technique. The research shows that partially only NPM and TATO have a positive and significant effect on earning growth, while simultaneously the four variables used have a positive and significant effect on stock returns.